The Roles of Tenascins in Cardiovascular, Inflammatory, and Heritable Connective Tissue Diseases - Matsumoto, Ken-ichi; Aoki, Hiroki (Frontiers in Immunology, 2020)
Tenascins are a family of multifunctional extracellular matrix (ECM) glycoproteins with time- and tissue specific expression patterns during development, tissue homeostasis and diseases. There are four family members (tenascin-C, -R, -X, -W) in vertebrates. Among them, tenascin-X (TNX) and tenascin-C (TNC) play important roles in human pathologies. TNX is expressed widely in loose connective tissues. TNX contributes to the stability and maintenance of the collagen network, and its absence causes classical-like Ehlers-Danlos syndrome (clEDS), a heritable connective tissue disorder. In contrast, TNC is specifically and transiently expressed upon pathological conditions such as inflammation, fibrosis and cancer. There is growing evidence that TNC is involved in inflammatory processes with proinflammatory or anti-inflammatory activity in a context-dependent manner. In this review, we summarize the roles of these two tenascins, TNX and TNC, in cardiovascular and inflammatory diseases and in clEDS, and we discuss the functional consequences of the expression of these tenascins for tissue homeostasis.